Using machine learning algorithms for diagnostics of moving equipment control systems - Tretiak, O. (Energy and Automation, 2025)
The article investigates the application of machine learning algorithms for automated diagnostics of mobile equipment control systems. The relevance of the work is due to the growing complexity of control systems, where the failure of individual components can lead to significant economic losses and safety threats. In the conditions of modern industrial production and transport, the need to create automated solutions for monitoring the technical condition is especially important. The purpose of the research is to develop and implement machine learning methods to increase the efficiency of detecting and predicting failures in control systems. The tasks of the work include creating models based on deep neural networks, training them on data about the operation of control systems, and assessing their performance. Analysis of control system operation data obtained from mobile equipment sensors, creation and testing of machine learning models are taken as research methods. Open source data and synthetically generated sets were used for experiments. The main tools were neural networks such as LSTM and CNN, which are implemented in the TensorFlow and PyTorch frameworks. The study was conducted using computing clusters to speed up training. The results of the study showed that the use of machine learning allows achieving high accuracy in technical condition diagnostics. For example, LSTM models provided failure prediction accuracy of up to 95%, while CNN effectively identified anomalies in real time. A comparative analysis was conducted with classical machine learning methods, which demonstrated the advantages of deep neural networks in terms of speed of adaptation to new data and noise resistance. At the same time, the main challenges remain the need for large amounts of data for training models and ensuring their energy efficiency when used in real conditions. Key words: machine learning, control system diagnostics, neural networks, failure prediction, maintenance automation